Intelligent agents driving computer generated forces for simulating human behaviour in urban riots. (18th July 2012) - Bruzzone, Agostino G.; Tremori, Alberto; Tarone, Federico; Madeo, Francesca
Over the last decade the authors have been working on several researches concerning the use of intelligent agents for managing simulation of critical situations in security, such as managing civil disorders, riots or terrorist actions. The adoption of intelligent agents to reproduce human behaviour is a key factor to implement realistic models for security and civil protection. Human behaviour is very complex to be simulated and it is important to early test final results to get consistent models. In this paper is described the use of early testing procedures to anticipate results before the VV&A phase. It is, in fact, useful to adopt this kind of early testing activities in application of intelligent agents with human behavioural models.